Perinatal outcomes after induced termination of pregnancy by methods: A nationwide register-based study of first births in Finland 1996-2013. - Situ Kc; Elina Hemminki; Mika Gissler; Suvi M Virtanen; Reija Klemetti (PLoS ONE)
Background Women with previous terminations of pregnancy (TOPs) before their first birth have been associated with poorer perinatal outcomes. However, previous studies on the perinatal outcomes by the method in previous TOPs are inconsistent. Objective To examine the perinatal outcomes of the first-time mothers with singleton births, by the method of previous TOP (medical and surgical vs no TOP, and surgical vs medical). Method This is a nationwide register-based study including 419,879 first-time Finnish mothers with singleton birth during the time period 1996-2013. Mothers having their first birth were identified from the Medical Birth Register and linked to the Abortion Register by their identification numbers. Multinomial logistic regression analysis was performed to examine the risk for preterm birth, low birth weight, small for gestational age and perinatal death by the method in previous TOPs. Results Among the first-time mothers, 87.0% had no history of TOPs, 3.2% had a history of medical TOP(s), 9.2% had a history of surgical TOP(s) and 0.6% had a history of both (medical and surgical) TOP(s). No significant differences in perinatal outcomes were found among the women with surgical TOPs, compared to the women with no TOPs. In unadjusted analysis, increased odds for preterm birth and low birth weight were found when comparing women having previous surgical TOPs with medical TOPs. Even after the adjustment of potential confounders, odds for preterm birth < 37 weeks (OR = 1.19, 95% CI = 1.04-1.36) and low birth weight < 2500 g (OR = 1.16, 95% CI = 1.00-1.35) remained significant. After restricting data to the single TOP, the results were similar; OR for both preterm birth and low birth weight was 1.18 (95% CIs = 1.02-1.36 and 1.01-1.38). Conclusion Perinatal outcomes did not differ among the mothers with surgical TOPs compared to the mothers with no TOPs, while the outcomes were poorer after surgical TOP(s) than after medical TOP(s).